Atomic‐scale characterization of the equilibrium β phase in Mg‐Nd‐Y alloy by means of HAADF‐STEM. Issue 6 (27th April 2016) - Zheng, Jingxu; Chen, Bin
Summary: The β phase in Mg‐Nd‐Y alloy, which forms during isothermal ageing, is proved to be Mg41 Nd5 by energy‐dispersive X‐ray spectroscopy (EDS) results as compositional evidence and by atomic‐scaled high angle annular dark field–scanning transmission electron microscopy (HAADF‐STEM) direct images from [001] β, [ 11 1 ¯ ] β, and [ 3 ¯ 11 ] β as structural evidence. SCANNING 38:743–746, 2016. © 2016 Wiley Periodicals, Inc.